Characterisation of Itersonilia spp. from Parsnip and Other Hosts - Lauren H. K. Chappell; Guy C. Barker; John P. Clarkson (Journal of Fungi)
Parsnips (Pastinaca sativa) are a speciality UK crop with an economic value of at least 31M GBP annually. Currently, the major constraints to production are losses associated with root canker disease due to a range of fungal pathogens, among which Itersonilia pastinacae is of most concern to growers. With limited research conducted on this species, this work aimed to provide a much-needed characterisation of isolates from across the UK, continental Europe, and New Zealand. Previously, up to four separate Itersonilia species have been proposed based on the formation of chlamydospores and host specificity: I. pastinacae, I. perplexans, I. pyriformans, and I. pannonica. However, Itersonilia spp. isolates principally from parsnip, but also from a range of other hosts, which were found to infect both parsnip roots and leaves in pathogenicity tests. In growth rate assays, isolates were found to grow at temperatures of 0–25 °C and produce both chlamydospores and ballistospores across the same range of temperatures, although chlamydospore production was found to decrease as temperature increased. Following whole genome sequencing, specific primers were designed for the molecular characterisation of the isolates using six housekeeping genes and three highly variable functional genes. Phylogenetic analysis separated isolates into two and six clades, respectively, but the grouping was not associated with hosts or locations. Based on the results of this research, there was no evidence to support more than a single species of Itersonilia among the isolates studied.